Smart city converged and accessed network based on 5G mobile communication system - Dapeng WU; Junjie YAN; Peng YANG (Dianxin kexue)
The development and construction of smart cities largely depend on the communication network infrastructure，and the latest 5G mobile communication system can sufficiently facilitate the revolution of communication network infrastructure for smart cities.The 3-layer network architecture for smart cities was introduced and the key issues of converged networks，such as the relationship evaluation，trust management and reliability assurance were holistically analyzed.Lastly，the corresponding solutions were given，which could enhance the application bearing capabilities of smart city communication networks.